Vigilantism as community social control: Developing a quantitative criminological model - Weisburd, David (Journal of quantitative criminology, 1988)
This paper presents the first systematic quantitative examination of participation in vigilante behavior. Data collected as part of a larger study of Jewish settler violence in the Israeli-controlled West Bank region are used to analyze the factors that lead members of a community to become involved in vigilante violence. Using logistic regression techniques it is found that settlers who fulfill requirements of the vigilante role and those located in outposts where the demand for vigilantes is greatest are most likely to be involved in vigilante activities. In conclusion, it is argued that these findings provide strong support for a criminological model of vigilante behavior that emphasizes the role of the vigilante as an agent of community social control.